Iron deficiency and fatigue in inflammatory bowel disease: A systematic review. - Stephanie Sartain; Maryam Al-Ezairej; Martin McDonnell; Catherine Westoby; Vasiliki Katarachia; Stephen A Wootton; J R Fraser Cummings (PLoS ONE)
Background It is unclear what impact iron deficiency has on fatigue in people with inflammatory bowel disease (IBD). This systematic review examined the evidence of whether iron deficiency, with or without anaemia, was associated with fatigue in IBD. Fatigue is a common symptom in patients with IBD that can be difficult to manage and treat. A greater understanding of the role and contribution of iron deficiency to fatigue may help improve the management of this condition. Methods The databases searched were MEDLINE, OVID, CINAHL and Web of Science. Inclusion criteria were studies measuring iron status for iron deficiency (ID) and patient-reported outcome measures (PROMs) for fatigue in patients with IBD of any level of disease activity. Assessment of bias was conducted using the Newcastle Ottawa Scale. Studies were grouped for syntheses according to whether exposure was iron deficiency without anaemia (IDWA) or ID regardless of haemoglobin level. Results Two hundred and eighty-five individual database results were identified and screened; 32 complete records were reviewed, from which seven studies with 1425 individuals were deemed eligible for inclusion in the results synthesis. Considerable variation in the methods and statistical analysis used to investigate the relationship between ID and fatigue prevented any quantitative synthesis. Studies varied by population disease activity levels, approaches used to define ID and PROMs used to measure fatigue. Three studies directly compared fatigue scores in IDWA to those not iron deficient, two of which showed patients with IDWA had significantly lower fatigue scores. Four studies used ID irrespective of anaemia as the exposure and reported mixed results on fatigue, with only one study reporting a higher prevalence of fatigue in the ID group. Conclusions There was marked heterogeneity between studies in this review. Two studies found evidence of a slight increase in fatigue levels in patients with IDWA. Though this does not explain all fatigue in patients with IBD, iron replacement should be considered to improve fatigue in iron-deficient patients.